A Study of Legal Protection for Victims of Gender-Based Violence in Digital Spaces from a Human Rights Perspective - Dian Rahadian; Evy Indriasari; Lely Setyawati Kurniawan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
This study examines the inadequacy of legal protection for victims of gender-based violence in digital spaces, emphasizing its implications from a human rights perspective. Using a library-based legal research method, data were collected from scholarly literature, legal documents, and international human rights instruments such as the UDHR and CEDAW. The findings reveal that online gender-based violence reflects structural gender inequality embedded within both digital systems and national legal frameworks. Existing laws, including Indonesia’s cyber and sexual violence statutes, remain fragmented and lack a human rights–based foundation. The study concludes that integrating feminist legal theory and human rights principles into digital governance is essential to ensure dignity, equality, and justice for all users in the evolving digital environment.